Sociocultural-based Subject-Specific-Pedagogy as an Effort to Strengthen the Pancasila Student Profile - Maryono; Hendra Budiono; Eka Sastrawati; Issaura Sherly Pamela (Jurnal Pendidikan Indonesia, 2023)
The development of sociocultural-based subject-specific pedagogy is an important approach in increasing understanding and appreciation of Pancasila values at the elementary school level. This approach integrates social, cultural and contextual aspects in learning subjects related to Pancasila. Sociocultural pedagogy equips students with the knowledge and skills to apply these values in various aspects of their lives, which can lead to positive societal change. Sociocultural pedagogy encourages the development of real-world skills such as communication, problem-solving, and teamwork, which are essential for applying Pancasila values in practical situations. This research aims to produce a sociocultural-based Subject Specific Pedagogy product as an effort to strengthen the profile of Pancasila students in elementary schools. This research is research and development with the development method used, namely the 4D model. The subjects of this research were validators, teachers and fourth grade elementary school students. The types of research data are qualitative and quantitative data. The data collection instruments are validation questionnaires and practicality questionnaires. The research results show that the product developed has a product validity of 3.99 in the Valid category, and a practicality level of 4.32 in the very practical category. It can be concluded that the sociocultural-based Subject Specific Pedagogy product as an effort to strengthen the Pancasila student profile of elementary school students is suitable for use in the learning process.